Therapeutic inertia in osteoporosis in postmenopausal women - Cruz da Silva, Mariana (2024)
Introduction: Osteoporosis (OP) is the most frequent metabolic bone disease, associated with fragility fractures and increased morbimortality. Despite population aging, there has been a downward trend in the implementation of anti-osteoporotic therapy. Objectives: To determine the therapeutic inertia in OP in postmenopausal women in primary health care. Verify whether age, T-score, the FRAX value, and anti-osteoporotic therapeutic inertia are associated. Methods: Cross-sectional observational study. Inclusion criteria: women aged between 55 and 85 coded with OP (ICPC-2 – L95) or fractures (ICPC-2 – L72-76) in the list of problems. A simple random sample was selected. Therapeutic inertia was defined based on the Portuguese Society of Rheumatology recommendations. Results: A sample of 217 patients was obtained. Therapeutic inertia was found in 17.5% of women, which increased to 48.6% in those who suffered fractures (p<0.001). There was a statistically significant difference between the ages of patients with and without therapeutic inertia (77.5 vs 73.0, p<0.010). The median FRAX for major osteoporotic fracture (16.5 vs 9.65, p<0.001) and hip fracture (7.6 vs 3.3, p<0.001) was higher in the group with therapeutic inertia. The difference between T-score values ​​for the lumbar spine (2.45 vs 2.71) and the femoral neck (2.07 vs 2.02) did not reach statistical significance (p=0.299). Conclusion: This study highlights the application of the most recent national guidelines regarding osteoporosis treatment in the studied health care unit, but underlines the need for broader intervention in osteoporosis-related fractures and at older ages.